Microbiostratigraphy of the Sagara Group, Shizuoka Prefecture, Japan - 尾田, 太良 (東北大學, 1971)
application/pdf The Tertiary deposits distributed in the Sagara district, Shizuoka Prefecture, are classified into the Megami Formation and the Sagara and Kakegawa groups in the named order from the older to the younger. The stratigraphical classification and biostratigraphic characteristics of the stratigraphic units are shown in Table 2, and briefly outlined below. The Megami Formation, the oldest of the recognized units, consists of hard mudstone, sandstone and limestone and is in fault contact with the Sagara Group. The Megami Formation corresponds to the major part of the Saigo Formation of the Mikasa Group distributed in the northern part of Kakegawa City and is correlated with the planktonic foraminiferal Zone N. 8 (Globigerinoides sicanus/Globigerinatella insueta Partial range zone) of Blow (1969). According to Blow (1969), the geological age is Early Miocene (Burdigalian). The Sagara Group comprises two formations each consisting of alternations of siltstone and sandstone, intercalated with conglomerate. The Kakegawa Group is composed of alternations of sandy siltstone and sandstone, intercalated with conglomerate and massive mudstone and lies with conformity upon the Sagara Group. The Sagara and Kakegawa groups have yielded many species of Foraminifera. In this district, zonation by means of the planktonic Foraminifera was previously made by Saito (1963). From the confirmation of a difference of the extinction level between Globigerina nepenthes and Sphaeroidinellopsis seminulina, Saito referred the Sagara Group and the lower part of the Kakegawa Group to the Globorotalia menardii menardiilGlobigerina nepenthes zone of Blow (1959) and assigned the lower to middle part of the Uchida Formation of the Kakegawa Group to the Sphaeroidinellopsis seminulina zone of Blow; he considered that these zones were correlative of the zones of the same name established in the Pozbn Formation, Venezuela by Blow (1959). Blow (1959) used the horizon of extinction of Globigerina nepenthes and Sphaeroidinellopsis ...